OPTIMIZATION OF TOURISTANT ASV WITH JACOBIAN APPROACH - Teguh Herlambang; Diecky Adzkiya; Hendro Nurhadi (JOURNAL ASRO, 2019)
An Autonomous Surface Vehicle (ASV) is an unmanned ship that can automatically navigate itself in watery area. ASV can be utilized as tourism modes, transportation modes, Indonesian military (TNI) fleets or warships. In this paper, the study used a Touristant ASV prototype with a length of 3 meters, a diameter of 1.5 meters, and a height of 1.3 meters. The ASV motion system is a linear model with 3-DOF (surge, sway and yaw), resulted from the linearization of the ASV nonlinear model into a linear model which, then, was optimized as the basis of the navigation and guidance control system. The objective of this paper is to check the controllability and observability of the ASV Touristant linear model. The contribution of this paper is to provide numeric study on the controllability and observability of the model. Keyword: ASV, 3-DOF, linear model, Optimization, Controlable, Observable